Institutions Serving Philippine International Labor Migrants - Aniceto Jr. C. Orbeta; Michael R. Cabalfin; Michael Ralph M. Abrigo (Philippine Institute for Development Studies (PIDS), 2009)
This paper discusses public and private institutions that were established in the Philippines to provide services to Filipino international migrant workers. Thirty years of having explicit policy on international labor migration has resulted to the creation of various public agencies to promote, manage, and protect migrant workers. This paper looks at their evolution and at the letter and application of their mandates as well as how some have become models for many developing countries to follow. It presents how government migration services work together with nongovernment organizations in a complementary manner in order to be able to provide support to Filipinos working and living overseas. It also shows how these institutions cover all aspects of migration including but not limited to predeployment, deployment, onsite support services, and eventual return.
Keywords: J61; J68; 330; Philippines; international labor migration; institutions; Arbeitsmigranten; Institutionelle Infrastruktur; Philippinen